A prospective, randomized comparative study of monopolar transurethral resection of the prostate versus photoselective vaporization of the prostate with GreenLight 120-W laser, in prostates less than 80 cc. (February 2015) - Telli, Onur; Okutucu, Tolga Muharrem; Suer, Evren; Burgu, Berk; Gulpinar, Omer; Yaman, Onder; Bozkurt, Selen
Objective: In this study we aimed to compare photoselective vaporization (PVP) with the GreenLight 120-W Laser and monopolar transurethral resection as surgical treatments of prostates less than 80 cc in men with obstructive benign prostatic hyperplasia. Methods: From February 2009 to March 2012 we allocated 101 patients with a prostate glands of less than 80 cc; patients were randomly assigned for surgical treatment with monopolar transurethral resection of the prostate (TURP) ( n = 62) or PVP ( n = 39). Serum prostate specific antigen (PSA), International Prostate Symptom Score (IPSS), Sexual Health Inventory for Men (SHIM), maximum flow rate (Qmax ) postmicturition residual (PMR), transrectal ultrasound volumes (TRUS), postvoid urine residual (PVR), complications, re-operations and hospitalization time were collected. The patients were seen in the follow up at 6, 12 and 24 months. Results: Median age was 69 (56–87) years old in the TURP group and 67 (51–87) years old in the PVP group. Mean preoperative prostate volume was 55 cc (40–72) and 60 cc (41–75) cc in the TURP group versus the PVP group. There was no statistically difference in subjectively (IPSS, SHIM) and objectively (Qmax -PMR) parameters and postoperatively complication rates between the two groups ( p > 0.05). A significant difference was observed in the PVP group with a 2 (1–4) days hospital stay compared with 5 (3–9) days for the TURP group ( p < 0.001). Conclusion: Prostate PVP and TURP are effective surgical treatments for benign prostatic hyperplasia. Postoperative functional improvements were durable and equivalent in the two groups. The two techniques have a similar complication rate.